Performance Analysis of Gray-Coded DP-16QAM MIMO-FSO Systems With Coherent Detection and DSP Techniques - Zinegnaw Libisework Gelaw; Pushparaghavan Annamalai; Hailu Dessalegn Ayalew (Journal of Computer Networks and Communications)
The performance of a gray-coded dual polarization-16 quadrature amplitude modulation (DP-16 QAM)–based multiple input multiple output (MIMO)-FSO link using coherent detection and digital signal processing (DSP) is investigated. The MIMO link is used to mitigate geometric loss, atmospheric attenuation, and atmospheric turbulence. Additionally, a coherent receiver with DSP algorithms is used to improve channel capacity, receiver performance, and link range. The performance of the system is evaluated by constellation diagrams, RF and optical power spectra, bit error rate (BER), and error vector magnitude (EVM). It is observed that before DSP, the constellation diagrams are distorted, whereas after DSP, distinct constellation symbols are observed. The system possesses a spectral efficiency of around 4.62 b/s/Hz. The longest link range to attain the acceptable BER limit is achieved under 4 × 4 MIMO weak turbulence levels in clear air conditions, which is 11.55 km, while the shortest is achieved under SISO strong turbulence levels in light fog conditions, which is 0.895 km. After the channel impairments are mitigated by DSP, the simulation results show that the MIMO link outperforms the SISO link in all scenarios.